Penguatan Peran Generasi Muda Baduy dalam Pengambilan Keputusan Berbasis Kearifan Lokal Menghadapi Perubahan Sosial - Restu Fauzi; Mardiana Mardiana; Diar Putra Lesmana; Risma Nur Amaliah; Nur Annisa Ramadhani (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This Community Service Program aims to strengthen the role of Baduy youth in decision-making based on local wisdom in facing social change. Baduy youth hold a strategic position as successors of cultural values; however, they also face challenges due to increasingly dynamic social changes. Therefore, strengthening efforts are needed to ensure that they are able to preserve traditional values while adapting to contemporary developments. This activity was conducted in Kanekes Village, Lebak Regency, on April 17, 2026, using participatory, educational, and collaborative approaches involving customary leaders and Baduy youth as the main partners. The implementation methods included socialization sessions, group discussions, and simulations of decision-making based on local wisdom. The results show an increase in the understanding and involvement of youth in recognizing the importance of local wisdom as a foundation for decision-making. The participatory approach proved effective in enhancing awareness and encouraging active participation of youth in preserving cultural values. In conclusion, this program successfully strengthens the role of Baduy youth as both cultural preservation agents and social adaptation actors in responding to ongoing social change.